(untitled) (Bangladesh Journal of Scientific Research, 2014)
Sewage sludge at the rate of 0, 40, 80, 120 and 240 t/ha showed that the number of filled grains per panicle, dry weight of grains and weight of 1000 grains of rice (Oryza sativa L.) were the significantly highest where 240 tons of sewage sludge per hectare was added. The contents of N, P, K, Ca, Mg, Fe, Cu, Zn and Pb in rice grains increased significantly with increasing rate of sewage sludge application, while that of Mn decreased significantly. Chromium, cadmium and nickel contents in the rice grain were below detection limit. DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20231 Bangladesh J. Sci. Res. 26(1-2): 57-60, December-2013